Fatiga de un acero AISI/SAE 5160 con temple interrumpido - Lozano de la Garza, Diego Emilio (2013)
AISI 5160 steel is used for the production of coil and leaf springs. Springs are usually oil-quenched and tempered. In this work, a brine solution is used as a quenchant. The brine promotes a more severe and uniform quenching. The severity of the quenching was analysed, and the heat transfer characteristics determined. A brine interrupted quenching was developed to produce a martensite case with a bainite core. The effect of various conditions after the interruption of the cooling is addressed. Tempering temperatures of 150, 250, 350 , 450 and 550 °C were employed. In addition, a partial decarburisation was promoted in the samples prior to the quenching and tempering, this in order to modify the local martensite start temperature and promote the martensite transformation to take place at a higher temperature, while reducing the amount of retained austenite. To determine the fatigue properties of heat treatments, a rotating bending fatigue tester with constant deflection was developed. Fatigue results showed that the interrupted brine quenching with partial decarburisation has a higher fatigue limit that the case with no decarburisation and also that the case of conventional oil quenching and tempering. Fractography and load data from experiments allowed to model the cracking stages. The model was useful to establish the presence of cracks and their length. It was found that when a martensite case and a pearlite core was produced, nucleation was retarded up to 5 times, however after a crack nucleates it propagates much rapid than in bainite.